ECONOMETRIC ANALYSIS OF THE INFLUENCE OF RISK FACTORS ON FARM ACTIVITIES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article discusses issues related to yield risks that arise in the activities of farms. The factors causing crop risk in farms were assessed and analyzed based on econometric methods. It is established that the regions of Namangan region of the Republic of Uzbekistan correlate with the indicators of cotton and wheat yields. The territorial interrelation of risks was analyzed. A proposal and recommendations have been developed to reduce the risk to productivity on farms.